Identification of a novel genetic element in Escherichia coli K-12. - Greener, A (1980)
Induction of the SOS repair processes of Escherichia coli K-12 caused a 14.4-kilobase species of circular deoxyribonucleic acid, called element e14, to be excised from the chromosome. To aid further characterization of this species, an 11.6-kilobase segment of e14 was inserted into the HindIII site of plasmid pBR313. To map e14 on the E. coli K-12 chromosome, the recombinant plasmid, pAG2, was used to transform a polA recipient, an event which required integration of pAG2 into the recipient chromosome. This recombinational event was dependent upon the region of homology between the incoming plasmid and the chromosome, as no transformants were scored when either a strain cured of the element was the recipient or pBR313 was the transforming deoxyribonucleic acid. Using these transformants, we have shown that e14 maps between the purB and pyrC loci near min 25. Several strains of E. coli K-12 were found to contain e14; however, one strain, Ymel trpA36, did not. In addition, e14 was found to be absent in both E. coli B/5 and E. coli C. The approach to mapping developed for this work could be used to map other fragments of E. coli deoxyribonucleic acid which have no known phenotype.